1996
DOI: 10.1115/1.2817785
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of Instabilities in Laminar Boundary Layers—Overview and Concept Validation

Abstract: This paper (the first in a series) focuses on using active-control methods to maintain laminar flow in a region of the flow in which the natural instabilities, if left unattended, lead to turbulent flow. The authors review previous studies that examine wave cancellation (currently the most prominent method) and solve the unsteady, nonlinear Navier-Stokes equations to evaluate this method of controlling instabilities. It is definitively shown that instabilities are controlled by the linear summation of waves (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…19 They showed that it was possible to delay accelerate transition by superposing disturbances out of in phase with the primary TS wave. Similar results were also reported by Danabasoglu et al 20 Finally, Joslin et al 21 performed a numerical experiment which served to unequivocally demonstrate the link between linear superposition and instability suppression. To ensure that linear superposition of individual instabilities was, in fact, responsible for the results found in previous experiments and computations, they carried out three simulations with i only the disturbance; ii only the control; and iii using both disturbance and control, which is the wave-cancellation case.…”
Section: The Wave-cancellation Conceptsupporting
confidence: 70%
See 2 more Smart Citations
“…19 They showed that it was possible to delay accelerate transition by superposing disturbances out of in phase with the primary TS wave. Similar results were also reported by Danabasoglu et al 20 Finally, Joslin et al 21 performed a numerical experiment which served to unequivocally demonstrate the link between linear superposition and instability suppression. To ensure that linear superposition of individual instabilities was, in fact, responsible for the results found in previous experiments and computations, they carried out three simulations with i only the disturbance; ii only the control; and iii using both disturbance and control, which is the wave-cancellation case.…”
Section: The Wave-cancellation Conceptsupporting
confidence: 70%
“…From the wave-cancellation study of Joslin et al, 21 the relationship between amplitude of the actuator v a with resulting instabilty can be shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the results, however, report incomplete destruction of instability waves. Joslin et al (1994) explain that wave cancellation is very sensitive to the wave parameters and postulate that incomplete destruction reported in past studies was due to improper phase or amplitude properties of the cancelling wave.…”
Section: Introductionmentioning
confidence: 99%
“…A nice survey of past work is given in Joslin, Erlebacher & Hussaini (1994). The basic idea is that boundary layer instabilities appear as a combination of many sinusoidally growing waves of certain frequencies, phases, and amplitudes.…”
Section: Introductionmentioning
confidence: 99%